Imagine the World you Want to Live in: A Study on Developmental Change in Doctor-Patient Interaction - Engeström, Ritva (Outlines. Critical Practice Studies, 1999)
The article focuses on talk and cognition in terms of action. It outlines methodological alternatives for approaches addressing meaning construction and the accounts people give of their actions. There are studies, rooted especially in phenomenology and ethnomethodology, that manifest the idea of intersubjective reality seen as achievements of situated actions. In this framework, conversation and communication are seen per se as significant forms of social action. Instead of intersubjective reality, often brought about with an inductive research method, the article argues for instrumental reality as the context for understanding talk and cognition in terms of action. The aim is a method that studies multivoicedness of activity in terms of situated actions. The method integrates situational features in dialogue with the cultural-historical processes of meaning construction. It is based on the theoretical notion of activity as a system that emerges and changes in time and place through internal contradictions. In the context of instrumentality, dialogical processes are also considered historically emerging and internally conflicting processes of rationality. I discuss this method with data on conversations between a patient and a doctor at a primary health care consultation. The study considers medical knowledge less as a substance than as a historically produced perspective through which the rationality of problem solving is accomplished by doctor and patient. The study aims to break away from the epistemological dualism of conflicting domains of meaning: the one of medicine that is objective and the one of experience that is subjective. The context of instrumentality includes a working hypothesis of a zone of proximal development of the doctor-patient relationship.